Conflicts of interest in neoliberal times: perspectives of Australian medical students. Issue 3 (1st September 2016) - Mayes, Christopher; Kerridge, Ian; Habibi, Roojin; Lipworth, Wendy
ABSTRACT: In this paper we report on the findings from six focus groups conducted with Australian medical students. The focus groups discussed students' perceptions of conflicts of interest and the influence of commercial values in health care and medical education. Our research revealed that students were aware of a number of structural influences that affected the medical education they received and that had the potential to shape their attitudes and practices as they progressed in becoming a doctor. We found that the pressures of educational workload and anticipated career trajectories tended to have an individualising effect that limited the perceived possibility of collective action and response to structural influences. We interpreted these findings through the lens of neoliberal governmentality to articulate the way commercial interests are negotiated and normalised by medical students. Based on these findings, we suggest that medical education should not only explicitly alert students to effects of political and commercial influences on the healthcare system, but also encourage the collective agency of students and strategies that do not place unrealistic expectations on individuals to effect structural change.